Primarna preventiva malignih tumorjev kože - zaščita pred sončnimi žarki - Benedičič-Pilih, Ana (Zdravniški vestnik, 2001)
Background. The incidence of skin cancer is increasing in the world as well asin our country. Decades of research have increased the understanding of the ethiopathogenetic influences and risk factors for development of malignant skin tumors and stimulated efforts to promote their prevention. There are successes of prevention programs in someplaces in the world expressing with the reduction of mortality because of the cutaneous malignant melanoma. A primary prevention of a skin cancer attemps to change population knowledge, attitudes and beliefs about sunlight, leading to reduce of sunlight exposure. Conclusions. In this article we are discussing guidelines for photoprevention.The best approach to it is a reduction in the overall exposureto sunlight. The natural protection with the use of shade, clothing and hats is promoted as the best protection. Sunscreens are assumed as an important component of adjuvant photoprotection based on their convenience of use and also on their widespread promotion. While it has been argued that all tanning is a manifestation of skin injury, avoiding of artificial tanning devices is proposed also.
Keywords: Kožne novotvorbe; kožni rak; Prevention and control; preventivna medicina; rak (medicina); Skin neoplasms; Sončenje, zaščita, zdravila; Sončna opeklina; Sunburn; Sunscreening agents; Ultravijolični žarki; ultravijolično sevanje; Ultraviolet rays